A Bargain for Frances. - Hoban, Lillian (New York, Harper & Row, 1970)
Thelma usually outsmarts Frances until Frances decides to teach her a lesson about friendship.
Keywords: Badgers -- Fiction; Friendship -- Fiction; Early chapter